Peranan Pupuk Organik dan NPK Majemuk terhadap Pertumbuhan Kelapa Sawit TBM 1 di Lahan Marginal - Sukmawan, Yan; ,, Sudradjat; ,, Sugiyanta (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2015)
ABSTRACTOil palm (Elaeis guineensis Jacq.) is the most efficient vegetable oil producer. It produces five to seven times more vegetable oil per hectare than the other vegetable oil producing crops. The objective of this research was to study the role of organic and NPK compound fertilizers application to one-year-old oil palm (Elaeis guineensis Jacq.) on marginal land. The research was conducted at IPB-Cargilll Teaching Farm of Oil Palm, Jonggol, Bogor, West Java from March 2013 to March 2014. The experiment was carried out as factorial experiment in a randomized block design with three replications. The first factor was organic fertilizer consisted of 0, 15, and 30 kg per palm. The second factor was NPK compound fertilizers 15:15:15 consisted of 0, 1.3 and 2.6 kg per palm. The results showed that no interaction effect between organic and NPK compound fertilizers on all of variables observed. Marginal soils in Jonggol required high rate of fertilizers to produce good performance of one-year-old oil palm. Application of 30 kg organic fertilizer per palm or 2.6 kg NPK compound fertilizers 15:15:15 per palm resulted in the highest vegetative growth of one-year-old oil palm on marginal land in Jonggol.Keywords: cow dung, critical nutrient level, slow release fertilizer, Ultisols, vegetative growth